2006 IEEE International Symposium on Information Theory 2006
DOI: 10.1109/isit.2006.262087
|View full text |Cite
|
Sign up to set email alerts
|

Degrees of Freedom for the MIMO Interference Channel

Abstract: Abstract-We explore the available degrees of freedom (DoF) for the two user MIMO interference channel, and find a general inner bound and a genie aided outer bound that give us the exact # of DoF in many cases. We also study a share-and-transmit scheme and show how the gains of transmitter cooperation are entirely offset by the cost of enabling that cooperation so that the available DoF are not increased.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
125
0
1

Year Published

2008
2008
2013
2013

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(128 citation statements)
references
References 11 publications
2
125
0
1
Order By: Relevance
“…According to (1) this is a proper system, and according to [9] it is infeasible because the information theoretic DoF outer bound value for this channel is only 8/3 per user. The DoF outer bound is easily found by allowing two of the users to cooperate fully, so that the resulting 2-user MIMO interference channel with (M 1 , N 1 , M 2 , N 2 ) = (8,16,4,8) has a total DoF value of 8 according to [11]. Since cooperation does not hurt, and linear schemes (or any other scheme for that matter) cannot beat an information-theoretic outer bound, it is clear that the (4 × 8, d) 3 linear interference alignment problem is infeasible for d ≥ 8/3, and in particular for d = 3. The observation that some proper systems are not feasible is also made by Cenk et al in [12] who suggest including known information theoretic DoF outer bounds to further expand the set of infeasible systems.…”
Section: Feasibility Of Linear Interference Alignment Without Time/frmentioning
confidence: 99%
See 1 more Smart Citation
“…According to (1) this is a proper system, and according to [9] it is infeasible because the information theoretic DoF outer bound value for this channel is only 8/3 per user. The DoF outer bound is easily found by allowing two of the users to cooperate fully, so that the resulting 2-user MIMO interference channel with (M 1 , N 1 , M 2 , N 2 ) = (8,16,4,8) has a total DoF value of 8 according to [11]. Since cooperation does not hurt, and linear schemes (or any other scheme for that matter) cannot beat an information-theoretic outer bound, it is clear that the (4 × 8, d) 3 linear interference alignment problem is infeasible for d ≥ 8/3, and in particular for d = 3. The observation that some proper systems are not feasible is also made by Cenk et al in [12] who suggest including known information theoretic DoF outer bounds to further expand the set of infeasible systems.…”
Section: Feasibility Of Linear Interference Alignment Without Time/frmentioning
confidence: 99%
“…Since cooperation does not hurt, and linear schemes (or any other scheme for that matter) cannot beat an information-theoretic outer bound, it is clear that the (4 × 8, d) 3 linear interference alignment problem is infeasible for d ≥ 8/3, and in particular for d = 3. The observation that some proper systems are not feasible is also made by Cenk et al in [12] who suggest including known information theoretic DoF outer bounds to further expand the set of infeasible systems. Interestingly, so far, all known DoF outer bounds for K user MIMO interference channels come directly from the DoF result for the 2-user MIMO interference channel [11], applied after allowing various subsets of users to cooperate, while eliminating other users to create a 2-user interference channel (as also illustrated by the preceding example). As we show in this work, these DoF outer bounds do not suffice, even for the symmetric 3-user MIMO interference channel for all M T , M R values.…”
Section: Feasibility Of Linear Interference Alignment Without Time/frmentioning
confidence: 99%
“…Thus, the MIMO interference channel of Figure 2(b) has a capacity region that contains the capacity region of the 3 user interference channel of Figure 1. Reference [17] has shown that the MIMO interference channel of Figure 2(b) has 1 degree of freedom meaning that its capacity is of the form log(SNR)+o(log(SNR)). Therefore, we have shown that…”
Section: The Gaussian 3 User Interference Channelmentioning
confidence: 99%
“…In a study of MIMO interference channels [3], the number of spatial degrees of freedom is defined as…”
Section: B Capacity Based Metricsmentioning
confidence: 99%
“…Clearly this is not what is required here, where it is exactly the effects of correlation on the channels that is of interest. Hence we propose the nonlimiting versions of DOF in [3] and [5] as…”
Section: B Capacity Based Metricsmentioning
confidence: 99%